2022
DOI: 10.3389/fgwh.2022.848401
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Antenatal Care Utilization Among Childbearing Women in Burkina Faso

Abstract: IntroductionAntenatal care (ANC) is one of the pillars of maternal and child health programs aimed at preventing and reducing maternal and child morbidity and mortality. This study aims to identify the factors associated with ANC use, considering both health care demand and supply factors in the single analysis.MethodsWe used data from the endline survey conducted to evaluate the impact of the performance-based financing (PBF) program in Burkina Faso in 2017. This study was a blocked-by-region cluster random t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…For occupational status, women who were currently employed compared to those who were unemployed showed a positive effect on having adequate ANC visits, and health facility delivery. These were supported by findings from previous studies that reported that employed women were more likely than unemployed women to attend ANC4 + visits [ 52 ], and deliver at health facility [ 53 ]. This could be because currently employed women have the financial means to afford health care services for their well-being and that of their future babies.…”
Section: Discussionsupporting
confidence: 83%
“…For occupational status, women who were currently employed compared to those who were unemployed showed a positive effect on having adequate ANC visits, and health facility delivery. These were supported by findings from previous studies that reported that employed women were more likely than unemployed women to attend ANC4 + visits [ 52 ], and deliver at health facility [ 53 ]. This could be because currently employed women have the financial means to afford health care services for their well-being and that of their future babies.…”
Section: Discussionsupporting
confidence: 83%
“…Low visit of antenatal care itself is argued to be linked to the poor quality of the antenatal care. A study in Burkina Paso found that women living in a health area where the level of ANC quality was high were three times more likely to use ANC services (OR: 2.96, 95% CI 1.46-6.12) than those in health areas with low ANC service quality [31]. High frequency of ANC visit is highly suggested, specifically, to pregnant mothers with short body height as it is a strategy to optimize mothers' health status and prevent babies' low birth weight that serves as a predictor of stunting.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancing ANC follow-up contacts among women of reproductive age is of utmost importance. Antenatal care is one of the pillars of maternal and child health programs aimed at preventing and reducing maternal and child morbidity and mortality 1 . It is the care provided to pregnant women by healthcare practitioners to identify maternal risks, prevent and manage complications, encourage positive health behaviours, and build a therapeutic patientprovider relationship 2 .…”
Section: Introductionmentioning
confidence: 99%